Predictors of inappropriate antimicrobial prescription: Eight-year point prevalence surveys experience in a third level hospital in Spain - Núñez-Núñez, María; Perez-Galera, Salvador; Girón-Ortega, José Antonio; Sandoval Fernández-Del-Castillo, Santiago; Beltrán-García, Margarita; De Cueto, Marina; Suárez-Barrenechea, Ana Isabel; Palacios-Baena, Zaira R.; Terol-Barrero, Pedro; Oltra-Hostalet, Fernando; Arenzana-Seisdedos, Ángel; Rodriguez-Baño, Jesús; et al. (Frontiers in Pharmacology, 2022)
Antibiotic stewardship programs (ASP) have already demonstrated clinical benefits. We aimed to describe the Point Prevalence Surveys (PPS) methodology implemented in our hospital as an efficient tool to guide ASP strategies. Annually repeated PPS were conducted from 2012 to 2019 at a 750-bed university hospital in South Spain. Key quality indicators and inappropriateness of antimicrobial treatment, defined strictly according to local guidelines, were described. Variables associated with inappropriate treatment were identified by bi/multivariable analysis. A total of 1,600 patients were included. We found that 49% of the prescriptions were inappropriate due to unnecessary treatment (14%), not first line drug recommended (14%), inadequate drug according to microbiological results (9%), unsuitable doses (8%), route (3%) or duration (7%). Samples collection presented a significant protective effect together with sepsis presentation at onset and intensive care unit admission. However, age, receiving an empirical treatment and an unknown or urinary source of the infections treated were independent risk factors for inappropriateness. Site and severity of infection were documented in medical charts by prescribers (75 and 61% respectively). PPS may allow identifying the main risk factors for inappropriateness. This simple methodology may be useful for ASP to select modifiable factors to be prioritized for targeted interventions.